Review of the renal endpoints used in cardiovascular safety clinical trials in type 2 diabetes mellitus patients and their importance in primary care - Górriz, Jose Luis (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2019)
• Diabetic kidney disease could be prevented. • Diabetic kidney disease progression to end-stage renal disease could be delayed. • The PC physician is actively involved in periodically renal assessment determination. • PC physicians should better know renal variables in order to manage accordingly. • Prevention of diabetic renal disease increases with early action.